Uczenie się dorosłych w hybrydowym modelu pracy - Marcin Rojek (Edukacja Ustawiczna Dorosłych, 2023)
This article presents part of the results of a study conducted in 2022/2023 on informal adult learning in a hybrid work model. This model frames the professional functioning of an increasing number of workers and is the source of their work experience. Among other things, the survey results reveal that the model is internally highly heterogeneous, is rapidly transforming and partly already exists in variants that were not yet theoretically described and mentioned in the literature when the survey was planned. The most diverse responses were obtained in the groups of statements concerning learning as action and learning as belonging. In contrast, the least variation occurred in the groups of statements on learning as becoming and experiencing. Switching to a hybrid work model most often increased commitment to work tasks, but at the same time made communication with colleagues more difficult. According to the respondents, the nature and intensity of social relationships between employees in the hybrid model are similar to those in the stationary model.